Effective GA approach for municipal solid waste collection: dynamic capacitated vehicle routing in smart cities. (24th April 2023) - Hentout, Abdelfetah; Maoudj, Abderraouf; Kouider, Ahmed; Aouache, Mustapha
Currently, municipal solid waste ( MSW ) collection is based on ineffective and inflexible static routing models done once a day by trucks. Given a set of fixed bins distributed over a specified area, trucks move along their predefined routes to collect the bins contents. It is also revealed that logistics costs for collection and recycling represent 95% of total cost; thus, minimising total travelled distances using minimum vehicles is of a key importance. This paper presents a genetic algorithm -based solution for municipal solid waste collection and monitoring at smart cities modelled as a capacitated vehicles routing problem ( CVRP ). This solution adopts two crossover techniques and three mutation methods applied on the population divided into three subsets. Experimental results over various benchmarks show the effectiveness and superiority of the proposed approach in terms of runtime and solution quality . Finally, a real case study of 50 sites (49 bins + a depot ) and ten trucks is deployed in the City of Baba Hassen, Algiers, Algeria .